Robust design : repertoire of biological, ecological, and engineering case studies - Jen, Erica (Proceedings volume in the Santa Fe Institute studies in the sciences of complexity., 2005)
Brings together 16 chapters by an eminent group of authors in a range of fields presenting aspects of robustness in biological, ecological, and computational systems. This volume also address robustness in biological, ecological, and computational systems.